Tanggung Jawab Notaris Terhadap Akta Pernyataan Keputusan Rapat Umum Pemegang Saham Perseroan Terbatas yang Tidak Memenuhi Syarat - Nunny Nurul Ariani; Taqiyuddin Kadir; Nurwidiatmo N (Postgraduate of Jayabaya University, 2019)
The creation of the GMS minutes in the form of a Notary deed called the Declaration of Resolution (PKR Deed) as an authentic deed, which is more intended to make it as a strong and absolute evidence, binding evidentiary power and as a perfect evidence so that there is no need to prove it with other evidences as long as the untruth cannot be proven. Notary deed is the main evidence in writing so that it becomes evidence in the court who had a very important position. The method used in this research is empirical legal research. Results of the research, in the making of PKR Deed, Notary is only responsible for the formal truth of the deed he made, not material truth. Basically, if formally what the Notary has done is in accordance with the procedure as stipulated in the law, the Notary must be very strong in its legal position in the sense that it has fulfilled the formal truth requirement which is its responsibility and in accordance with its authority. However, in the event that Notary commits an unlawful act in making a PKR Deed which not meet requirements as set out in regulations, then Notary must take responsibility associated with authentic deed he made